2019
DOI: 10.1002/aenm.201901286
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Solar Waterways: Plasma‐Enabled Self‐Cleaning Nanoarchitectures for Energy‐Efficient Desalination

Abstract: Evaporating seawater and separating salt from water is one of the most promising solutions for global water scarcity. State‐of‐the‐art water desalination devices combining solar harvesting and heat localization for evaporation using nanomaterials still suffer from several issues in energy efficiency, long‐term performance, salt fouling, light blocking, and clean water collection in real‐world applications. To address these issues, this work devises plasma‐enabled multifunctional all‐carbon nanoarchitectures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 47 publications
(129 reference statements)
1
96
0
Order By: Relevance
“…In this practical device, water productivity is low because of the limited water condensation process. The device can be further optimized with mechanical moving parts to enhance water productivity and salt crystals 16 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this practical device, water productivity is low because of the limited water condensation process. The device can be further optimized with mechanical moving parts to enhance water productivity and salt crystals 16 …”
Section: Resultsmentioning
confidence: 99%
“…The device can be further optimized with mechanical moving parts to enhance water productivity and salt crystals. 16…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that, with the rapid growth of vapor generation rate, the collection of condensate has been the Achilles's heel of solar distillation (Figure S22, Supporting Information). It is reported that reducing the pressure of evaporation chamber or separating the evaporation chamber and condensation chamber in space favor high efficient vapor collection.…”
Section: Resultsmentioning
confidence: 99%